EDUCATION SYSTEM IN UZBEKISTAN (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This article analyzes the current state of the education system of Uzbekistan, its stages of development, existing problems and their solutions. The process from preschool education to higher education, recent reforms and changes related to international experience are covered. The article discusses the quality of education, the personnel training system and the introduction of information technologies.